Case report: A case of neuro-Behçet's syndrome presenting as brain stem mass lesions - Ayoade, Folusakin; Hernandez, Salma; Montreuil, Nadine; Drews-Elger, Katherine; Quiroz, Tanya; Sternberg, Candice A. (Frontiers in Neurology, 2023)
Neuro-Behçet's syndrome, a severe and rare manifestation of Behçet's disease (BD), can be misdiagnosed due to its challenging clinical presentation. This article presents the case of a 20-year-old cis-gender male with intermittent fever, bilateral uveitis, and neurological symptoms who was found to have multiple brain stem mass lesions on brain imaging. A careful medical history elicited recurrent painful oral and genital ulcerations which were important in making the correct diagnosis. As there are no validated criteria or definite set of tests available to confirm neuro-Behçet's disease, the diagnosis is often established by exclusion after ruling out other potential etiologies. In our case, after an extensive negative workup for infectious, neuro-degenerative and malignant etiologies combined with the patient's medical history, a diagnosis of Behçet's disease with neurological involvement (neuro-Behçet's syndrome) was made. High doses of steroids were given, and the patient had a favorable outcome. Repeated magnetic resonance imaging of the brain 2 years later showed no new brain lesions. Neuro-Behçet's disease should be included as a differential diagnosis of unexplained brain stem lesions in the right clinical context. In these situations, providers should obtain medical histories related to genital and oral ulcers and eye problems as these may help to narrow down the diagnosis. The clinical presentation and challenges of this uncommon presentation of BD including a brief literature review of neuro-Behçet's disease with brain stem mass lesions are discussed in this case study.